Duration of infertility and assisted reproductive outcomes in non-male factor infertility: can use of ICSI turn the tide? - Liting Zhang; He Cai; Wei Li; Li Tian; Juanzi Shi (BMC, 2022)
Abstract Background Intracytoplasmic sperm injection (ICSI) is increasingly used among in vitro fertilization (IVF) cycles without male factor infertility. For couples with prolonged infertility duration, the preferred insemination method may vary across laboratories and clinics. We analyzed whether ICSI is effective for non-male factor infertility with long infertility duration. Methods Seventeen thousand four hundred seventy-seven IVF/ICSI cycles from women with non-male factor infertility were included, of these 4177 women with infertility duration ≥ 5 years were in the final analysis. Primary outcome was the live birth rate after first embryo transfer. Secondary outcomes were rates of clinical pregnancy and fertilization. Results A nonlinear relationship was observed between infertility duration and IVF fertilization rate, which decreased with infertility years up to the turning point (4.8 years). 4177 women with infertility ≥ 5 years were categorized by IVF (n = 3806) or ICSI (n = 371). Live birth rate after first embryo transfer was 43.02% in ICSI and 47.85% in IVF group (adjusted odds ratio (aOR), 0.91; 95% confidence interval (CI), 0.72-1.15). Fertilization rate per metaphaseII (aOR, 1.10; 95% CI, 0.86-1.40) and clinical pregnancy rate (aOR, 0.89; 95% CI, 0.71-1.13) were similar between the two groups. Sensitive analyses (women ≥ 35 years) did not show a benefit of ICSI over IVF. Conclusions Women with infertility exceeding 4.8 years had decreased incidence of IVF fertilization. The use of ICSI showed no significant improvement in fertilization and live birth rates for non-male factor couples with ≥ 5 years of infertility.